It Takes More Than a Good Camera: Which Factors Contribute to Differences Between Face-to-Face Interviews and Videoconference Interviews Regarding Performance Ratings and Interviewee Perceptions? - Johannes M. Basch; Klaus G. Melchers; Anja Kurz; Maya Krieger; Linda Miller (Journal of Business and Psychology, 2020)
Due to technological progress, videoconference interviews have become more and more common in personnel selection. Nevertheless, even in recent studies, interviewees received lower performance ratings in videoconference interviews than in face-to-face (FTF) interviews and interviewees held more negative perceptions of these interviews. However, the reasons for these differences are unclear. Therefore, we conducted an experiment with 114 participants to compare FTF and videoconference interviews regarding interview performance and fairness perceptions and we investigated the role of social presence, eye contact, and impression management for these differences. As in other studies, ratings of interviewees' performance were lower in the videoconference interview. Differences in perceived social presence, perceived eye contact, and impression management contributed to these effects. Furthermore, live ratings of interviewees' performance were higher than ratings based on recordings. Additionally, videoconference interviews induced more privacy concerns but were perceived as more flexible. Organizations should take the present results into account and should not use both types of interviews in the same selection stage.
Keywords: 650; Technology-mediated interviews; Impression management; Social presence; Privacy concerns; Job interviews; Applicant reactions